Gut colonization of semi-aquatic turtles inhabiting the Brazilian Amazon by international clones of CTX-M-8-producing Escherichia coli - Silva, Meire Maria da; Sellera, Fabio Parra; Furlane, Joao Pedro Rueda [UNESP]; Aravena-Ramirez, Valentina; Fuentes-Castillo, Danny; Fuga, Bruna; Froesi, Alexandre Jose dos Santos; Sousai, Alana Lislea de; Garino Junior, Felicio; Lincopan, Nilton (Elsevier B.V., 2024)
Extended-spectrum (3-lactamase (ESBL)-producing Escherichia coli poses a significant threat to public health due to its ability to confer resistance to broad-spectrum antimicrobials, especially third-generation cephalosporins. Herein, we report gut colonization by international clones of CTX-M-8-producing E. coli in scorpion mud turtles (Kinosternon scorpioides) from a captive breeding program in the Brazilian Amazon. The E. coli strains exhibited multidrug resistance to clinically relevant antimicrobials, and genomic analyses revealed broad resistomes to antimicrobials, heavy metals, pesticides, and disinfectants. Detecting these medically important bacteria in captive wildlife underscores the potential risks associated with reintroduction programs, as ESBL-producing bacteria may spill over into the natural ecosystem and threaten wildlife. Our findings highlight the need for enhanced surveillance and control measures in wildlife conservation programs to mitigate the risks of antimicrobial resistance transmission between captive and wild populations.
Keywords: Enterobacterales; ESBL; Genomic surveillance; Reptiles; Wildlife